Modelling enhancement-mode GaN HEMTs with graded AlGaN barrier, graphene passivation, and dual field plates via TCAD - Mohiminur Rahman Ifty; Abdullah Al Fahad; Arnab Talukder; Satyazit Ghosh; Piash Sharma; Md. Sadik Al Rayhan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
An enhancement-mode aluminum gallium nitride (AlGaN)/gallium nitride (GaN) HEMT is presented in which graphene-capped SiN passivation, a recessed composite p-GaN gate, dual discrete field plates, and a compositionally graded AlGaN barrier (35%→18% Al) are co-engineered in a single device. The novelty lies in integrating these four techniques within one enhancement-mode architecture to simultaneously suppress surface trapping and reduce gate leakage, strengthen electrostatic gate control, and redistribute the electric field for higher breakdown and more uniform field profiles. TCAD results indicate a threshold voltage (Vth) of +2.6 V, transconductance (gm) of 335 mS/mm, and breakdown voltage (Vbr) around 1 kV. The radio-frequency (RF) analysis shows a cut-off frequency (fT) of ~42.57 GHz, with favorable gate capacitance characteristics. These outcomes show that co-optimization delivers normally-off operation with improved breakdown and RF speed relative to using the techniques separately, supporting suitability for high-power, high-frequency applications.